Heterojunction Solar Cells: Remarkably High Conversion Efficiency of Inverted Bulk Heterojunction Solar Cells: From Ultrafast Laser Spectroscopy and Electron Microscopy to Device Fabrication and Optimization (Adv. Energy Mater. 11/2016). Issue 11 (8th June 2016) - Alsulami, Qana A.; Murali, Banavoth; Alsinan, Yara; Parida, Manas R.; Aly, Shawkat M.; Mohammed, Omar F.
Abstract : A profound understanding of the photophysical processes at donor/acceptor interfaces is integral for the optimization of the photo conversion efficiency (PCE) of solar cell devices. Time‐resolved laser spectroscopy and electron microscopic investigations provide the key information to accomplish high PCE in polymer‐fullerene‐based solar cells. This device optimization enhanced the PCE from 2% in IC60 BA‐based to >9% in PC71 BM‐based solar cells, as presented by Omar F. Mohammed and co‐workers in article number 1502356.